Phonetic resilience and linguistic transfer: An acoustic analysis of Jibbali (Shehri) influence on English vowel production - Al-Yafaei, Yasir; Muqaibal, Muna Hussain; Thomas, Aju; Mudhsh, Badri Abdulhakim (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the influence of Jibbali (Shehri) as a mother tongue on English vowel production, focusing on phonetic resilience and linguistic transfer. Mainly, the study aims to analyze how differences in the vowel systems of Jibbali and English affect articulation patterns among bilingual speakers in Oman, with implications for language education under Oman’s Vision 2040. The study involves 20 participants: 10 native Jibbali speakers from Dhofar who have learned English as a foreign language, and 10 native English speakers serving as a control group. Participants’ pronunciations of selected English vowels were recorded and analyzed using PRAAT, a recognized acoustic phonetics software. The focus was on formant frequencies (F1 and F2) to assess vowel quality and detect patterns of interference. Results reveal significant phonological transfer from Jibbali to English. Jibbali speakers showed consistent vowel centralization, with /iː/, /oʊ/, and /uː/ produced with F2 values closer to the central range. Furthermore, contrasts between short and long vowels (e.g., /ɪ/ vs. /iː/) were less distinct, indicating influence from Jibbali’s phonological system, which lacks equivalent vowel length distinctions. These findings highlight the challenges Jibbali-speaking learners face in mastering English vowel quality. The study offers valuable insights for educators and policymakers in Oman, emphasizing the need for targeted pronunciation instruction and culturally informed teaching approaches. Such efforts align with national goals to enhance English proficiency and educational quality as part of Oman’s Vision 2040.